2020
DOI: 10.1002/smll.202000597
|View full text |Cite|
|
Sign up to set email alerts
|

Layered Ca0.28MnO2·0.5H2O as a High Performance Cathode for Aqueous Zinc‐Ion Battery

Abstract: Aqueous zinc‐ion batteries are promising candidates for grid‐scale energy storage because of their intrinsic safety, low cost, and high energy intensity. However, lack of suitable cathode materials with both excellent rate performance and cycling stability hinders further practical application of aqueous zinc‐ion batteries. Here, a nanoflake‐self‐assembled nanorod structure of Ca0.28MnO2·0.5H2O as Zn‐insertion cathode material is designed. The Ca0.28MnO2·0.5H2O exhibits a reversible capacity of 298 mAh g−1 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
105
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(108 citation statements)
references
References 41 publications
(23 reference statements)
3
105
0
Order By: Relevance
“…As shown in the insert of Figure 1A, in the crystal structure of δ-MnO 2 , K + ions and H 2 O molecules reside in the interlayer space of MnO 6 layers. The pre-intercalated K + ions and H 2 O molecules can act as pillars to expand the interlayer distance and improve the structural stability (Wang et al, 2019b;Sun et al, 2020). The detailed valence states of Mn and C elements were investigated through XPS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the insert of Figure 1A, in the crystal structure of δ-MnO 2 , K + ions and H 2 O molecules reside in the interlayer space of MnO 6 layers. The pre-intercalated K + ions and H 2 O molecules can act as pillars to expand the interlayer distance and improve the structural stability (Wang et al, 2019b;Sun et al, 2020). The detailed valence states of Mn and C elements were investigated through XPS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…f) Structural illustration of the as‐prepared Ca 0.28 MnO 2 ·0.5H 2 O. Reproduced with permission. [ 85 ] Copyright 2020, Wiley‐VCH.…”
Section: Defect Engineering On Manganese‐based Oxidesmentioning
confidence: 99%
“…Sun and co‐workers preinserted Ca 2+ and water into layered δ‐MnO 2 to act as pillars. [ 85 ] It was reported that the incorporation of hydrated Ca 2+ could expand the interlayer spacing and stabilize the layered structure of Ca 0.28 MnO 2 ·0.5H 2 O. As such, this resulted in a significantly improved reversible insertion/extraction stability of Zn 2+ .…”
Section: Defect Engineering On Manganese‐based Oxidesmentioning
confidence: 99%
See 2 more Smart Citations